Implementation Of Time Value Of Money In The Pecotan Tradition Of The Paiton Community - Sohebatul Mukarromah; Muhammad Sulhan (Universitas Islam Lamongan, 2022)
This study aims to determine the implementation of the Time Value of Money contained in the Pecotan tradition of the Paiton community. The research method is descriptive qualitative and phenomenological. The informants in this study were the Paiton people because the Paiton people were still thick with the pecotan tradition and there were differences in how to invite the Paiton people to do pecotan. The results and conclusions are that the implementation of the pecotan tradition is carried out at the wedding reception, while the distribution of invitations for cigarettes and soap is given from one week to one month before the reception. women, young and old, known and unknown. The contract used in the pecotan tradition is a donation, and is sincere. andImplementation of Time Value of Money applies to money.